Acute Gastric Volvulus Causing Splenic Avulsion and Hemoperitoneum - Yana Cavanagh; Neal Carlin; Ruhin Yuridullah; Sohail Shaikh (Case Reports in Gastrointestinal Medicine)
Gastric volvulus is an abnormal, potentially life-threatening, torsion of the stomach. The presence of complications such as hemoperitoneum increases the diagnostic urgency; however it can also mask the presentation of gastric volvulus. We encountered a 66-year-old female who presented with symptomatic gastric outlet obstruction and was found to have hemoperitoneum and splenic avulsion on imaging. In our case, hemoperitoneum was a clinical red herring as initial imaging concentrated on the presence of hemoperitoneum and was nondiagnostic of gastric volvulus. Interestingly, our patient experienced complete resolution of her presenting symptomatology following placement of a nasogastric tube. Furthermore, endoscopic evaluation revealed no overt pathology to explain outlet obstruction. In light of these findings, gastric torsion was strongly suspected. A repeat CT scan was confirmatory, elucidated reduction of the stomach to its anatomic position, retroactively diagnosing a gastric volvulus. This case is unusual in its presentation and setting. The patient presented with two rare complications of gastric volvulus, hemoperitoneum and splenic avulsion. Additionally, ten years prior to this presentation the patient had a temporary gastrostomy tube. Gastropexy with a gastrostomy is the treatment for gastric volvulus and should have been preventative of her presentation with torsion. Furthermore, the gastric volvulus was not initially recognized radiographically due to the presence of masking radiographic findings. This case serves to highlight the utility of clinical acumen and maintain a high index of suspicion for gastric volvulus in all cases presenting with Borchardt’s triad.